Analisis Sedimen Urine pada Peminum Kopi di Kelurahan Titi Rantai Kecamatan Medan Baru Kota Medan - Budiarti Sembiring; Rosliana Lubis; Abdul Karim; Ferdinand Susilo (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2026)
Coffee is a widely consumed beverage containing caffeine and oxalate, which may affect urinary tract health. This study aimed to analyze urine sediment among coffee drinkers in Titi Rantai Village, Medan Baru District, Medan City. A quantitative descriptive method was employed with 56 respondents selected through purposive sampling. Urine sediment examination was conducted microscopically to identify erythrocytes, leukocytes, epithelial cells, casts, crystals, and calcium oxalate crystals. Data were analyzed descriptively using frequency and percentage distributions. The results showed that 38 respondents (67.86%) had normal urine sediment, while 18 respondents (32.14%) exhibited abnormal urine sediment. The most common abnormalities were erythrocytes (51.79%), followed by calcium oxalate crystals (39.29%) and other crystals (37.50%). Calcium oxalate crystals were detected in 24 respondents (42.86%), whereas 32 respondents (57.14%) showed no calcium oxalate crystals. In conclusion, most coffee drinkers had normal urine sediment; however, abnormal findings, particularly erythrocytes and calcium oxalate crystals, were still observed and may indicate potential urinary tract disorders.